Combining portable X-ray fluorescence and clustering methods for mineral exploration. A case study in Batigelas (Ossa-Morena Zone, Portugal) - NOGUEIRA, Pedro (2020)
Batigelas is a mineral occurrence in the Alter do Chão-Elvas sector of the Ossa-Morena Zone that was investigated by the Serviço de Fomento Mineiro including soil geochemistry and terrestrial geophysics. The results obtained justified the execution of a drill hole. Recent soil geochemistry work using portable X-ray fluorescence has yielded new results for the region. The application of clustering methods (hierarchical and k-means clustering) to the analyses allowed to detail not only the initial anomaly identified, but also to identify the outcropping of geological units in the region. The results obtained highlight the importance of applying this technique in mineral exploration campaigns.